(3fgGjI GdeQGe aj TQM GdeNJUQ GdfGaYs - (3GdYGedj, GdehShj, GdMGFQj, eMeO Ydj Hf CHj GdMSf Hf UGdM, J (B1290(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOG cKjQG jdjb HLdGdg(B... (3bhdg(B: (3cJGH GdfcGM, bGd GdLhgQj(B...s
(3BNQgG (B:s
(3abdJ ddg Ydi Cf dG CHjYgG CHOG hdj (B... (3eMehdI Ydi EPG de jHdZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B300s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B503s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis